A COMPARATIVE STUDY OF COLOUR PREFERENCES TOWARDS CLOTHING AMONG YOUNG GIRLS AND BOYS - Upadhayay, Ranjana (International Journal of Research -GRANTHAALAYAH, 2014)
Colour, is the visual perceptual property corresponding in human beings to the names called red, green, blue, and so on and so forth. Colours are derived from the spectrum of light, interacting in the eye with the spectral sensitivities of the light receptors. Colour categories and physical specifications are related to objects or materials based on their physical properties such as light absorption, reflection, or emission. The meanings of colors vary according to cultures and environments. Each color has many aspects which may be expressed as the language of color by understanding few concepts. Colour is a form of non-verbal communication. The perception of color stems from varying spectral sensitivity of different types of cone cells in the retina to different parts of the spectrum, and thus colors may be defined and quantified by the degree to which they stimulate these cells. The science of color is called chromatics, colorimetry, or simply color science. It includes the perception of color by the human eye and brain, the origin of color in materials, color in art, and the physics of electromagnetic radiation in the visible range (that is, what we commonly refer to as light).